2003
DOI: 10.1016/s0009-9236(03)00224-8
|View full text |Cite
|
Sign up to set email alerts
|

Gly389Arg polymorphism of β1-adrenergic receptor is associated with the cardiovascular response to metoprolol

Abstract: The Arg389 variant of the beta(1)-adrenergic receptor was associated with a greater response to metoprolol than that of Gly389 in young, male Chinese subjects. These data suggested that the beta(1)-adrenergic receptor Gly389Arg polymorphism is of major functional importance in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
5
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 30 publications
4
105
5
5
Order By: Relevance
“…In addition, our findings are largely consistent with the literature in that b 1 -AR codon 389 genotype does not appear to influence HR response to b-receptor agonists, antagonists or exercise, nor does it appear to affect resting HR. [4][5][6][18][19][20][21] Taken together, these data in myriad patient populations suggest that while the functional effects of the b 1 -AR codon 389 polymorphism have been documented in numerous settings, it seems now it may be clearly concluded that this polymorphism does not affect HR, or its responses to agonists, antagonists or exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our findings are largely consistent with the literature in that b 1 -AR codon 389 genotype does not appear to influence HR response to b-receptor agonists, antagonists or exercise, nor does it appear to affect resting HR. [4][5][6][18][19][20][21] Taken together, these data in myriad patient populations suggest that while the functional effects of the b 1 -AR codon 389 polymorphism have been documented in numerous settings, it seems now it may be clearly concluded that this polymorphism does not affect HR, or its responses to agonists, antagonists or exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have provided evidence for their functional basis, [1][2][3] and these polymorphisms have been implicated in differential response to b 1 -and b 2 -AR antagonists and agonists in numerous studies. Specifically, studies have shown that b 1 -AR genotype is a significant predictor of blood pressure and ejection fraction responses to b-blockers, [4][5][6][7][8] and responses to b 2 agonists have been associated with b 2 -AR polymorphisms. 9,10 Dobutamine is a potent synthetic intravenous inotrope that is principally an agonist at b 1 -AR with mild stimulatory effects at b 2 -AR and a 1 -AR.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studying the effects of atenolol and metoprolol on healthy volunteers, Liu et al (2003) and Sofowora et al (2003), respectively, found that Arg389 homozygous subjects showed larger decreases in systolic blood pressure and mean blood pressure than Gly389 homozygous subjects. In addition, Liu et al (2003) also reported greater metoprolol-evoked bradycardia in homozygous Arg389 than homozygous Gly389. Furthermore, homozygous Arg389 patients with end-stage heart failure, but not homozygous Gly389 patients, showed significant improvement of the left ventricular ejection fraction when treated with the b-blocker carvedilol (Perez et al, 2003).…”
Section: Introductionmentioning
confidence: 87%
“…There appears to be no association with the 389 polymorphism on the blood pressure or heart rate responses to b-blockers in the treatment of hypertension (O'Shaughnessy et al, 2000). In contrast, studying the effects of atenolol and metoprolol on healthy volunteers, Liu et al (2003) and Sofowora et al (2003), respectively, found that Arg389 homozygous subjects showed larger decreases in systolic blood pressure and mean blood pressure than Gly389 homozygous subjects. In addition, Liu et al (2003) also reported greater metoprolol-evoked bradycardia in homozygous Arg389 than homozygous Gly389.…”
Section: Introductionmentioning
confidence: 96%
“…While some groups reported enhanced β-blocker responses in homozygous carriers of the gain-of-function 389R allele in small studies (metoprolol: Liu et al 2003;Johnson et al 2003;atenolol: Sofowora et al 2003), others did not observe effects of the G389R and the S49G polymorphisms in the β1 adrenoceptor gene on β-blocker responses (Filigheddu et al 2004;Karlsson et al 2004;O'Shaughnessy et al 2000). A recent study reported 9% decreases in mean blood pressures for homozygous hypertensives with the 49S389R haplotypes, while blood pressure decreases were virtually absent in homozygous carriers of the 49S389G haplotypes or in 49S389G/ 49G389G diplotypes .…”
Section: Pharmacogeneticsmentioning
confidence: 99%